Prophylaxis of primary ventricular fibrillation with tocainide in acute myocardial infarction. Issue 6 (June 1983) - Campbell, R W; Hutton, I; Elton, R A; Goodfellow, R M; Taylor, E
Abstract : Within six hours of suspected acute myocardial infarction, 791 patients entered a randomised double blind study of combined intravenous and oral tocainide for the prophylaxis of primary ventricular fibrillation. Acute myocardial infarction was confirmed in 559 patients, of whom 278 had received tocainide. The study was terminated on the basis of a sequential statistical analysis which showed that in these patients tocainide was unlikely to reduce the incidence of primary ventricular fibrillation by as much as 50%, primary ventricular fibrillation having occurred in 4% of the tocainide and 2% of the placebo patients. Significantly fewer tocainide treated patients were withdrawn for other serious ventricular arrhythmias. Mortality (1% in the tocainide group and 2% in the placebo group) was low with no statistically significant differences between the active and placebo groups. Unwanted effects of treatment were infrequent and rarely troublesome both in patients with and without acute myocardial infarction. These results suggest that in the dosage used in this study tocainide does not exert an antifibrillatory action in the early phase of acute myocardial infarction.